2016
DOI: 10.1086/686631
|View full text |Cite
|
Sign up to set email alerts
|

The Political Legacy of American Slavery

Abstract: We show that contemporary differences in political attitudes across counties in the American South in part trace their origins to slavery's prevalence more than 150 years ago. Whites who currently live in Southern counties that had high shares of slaves in 1860 are more likely to identify as a Republican, oppose affirmative action, and express racial resentment and colder feelings toward blacks. These results cannot be explained by existing theories, including the theory of contemporary racial threat. To expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(125 citation statements)
references
References 41 publications
3
121
0
1
Order By: Relevance
“…The figures show the influence of lynching on perceived black criminal threat across levels of disadvantage and, separately, levels of percent voting Republican. 3 One reviewer, citing Acharya et al (2016), suggested that slavery may account for some of the effect of lynchings. In ancillary analyses, we included a county-level variable to account for the proportion of the black population who, according to the 1860 U.S. Census, were slaves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The figures show the influence of lynching on perceived black criminal threat across levels of disadvantage and, separately, levels of percent voting Republican. 3 One reviewer, citing Acharya et al (2016), suggested that slavery may account for some of the effect of lynchings. In ancillary analyses, we included a county-level variable to account for the proportion of the black population who, according to the 1860 U.S. Census, were slaves.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, greater attention is needed to ways in which other historical conditions may be relevant in understanding the effects of lynchings, racial threat processes, and contemporary views whites hold toward blacks. Acharya et al (2016), for example, have argued for the potential role that slavery, and competition among whites and blacks, may play in influencing whites' racial resentment, political affiliation, and views about affirmative action (see also Wells 1970). Although they found no evidence that slavery effects arose through racial threat processes, the study aligns with studies of lynchings in pointing to the persistent influence of the past.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, some scholars have found that voters in areas that were historically racist against Blacks are also more likely to vote for the Republicans, especially in the U.S. South. If historical legacy is correlated with modern opposition for immigrants, then voters' reactions could be reflecting historical prejudice rather than current response to unauthorized immigration (Acharya, Blackwell, & Sen, 2016;O'Connell, 2012;Reece & OConnell, 2016). The advantage of being able to use cross-sectional time-series data is that we are able to control for historical prejudice, as well as any other time-invariant correlates, through the inclusions of county fixed effects.…”
Section: Resultsmentioning
confidence: 99%